Fiber and method for manufacturing the same, and fiber structure and method for manufacturing the same

CN123022845APending Publication Date: 2026-10-30KANEKA CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202580023064.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-06
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]然而,PLA系树脂难以实现家庭堆肥,另外,存在海洋生物降解性缺乏之类的问题

Benefits of technology

[0026]根据本发明,可以提供能够形成不易破裂的纤维结构体的含有聚(3-羟基烷酸酯)系树脂的纤维、以及包含该纤维的纤维结构体。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present application provides a fiber containing a poly(3-hydroxyalkanoate)-based resin, which can form a fiber structure that is less likely to break. The present application provides a fiber, which contains a resin composition containing a poly(3-hydroxyalkanoate)-based resin and a polylactic acid-based resin, 50 to 99 parts by weight of the poly(3-hydroxyalkanoate)-based resin with respect to 100 parts by weight of the total of the poly(3-hydroxyalkanoate)-based resin and the polylactic acid-based resin, and the average value of the fiber diameter of the fiber is 5 μm or less, and in a cross section of the fiber, there is no sea-island junction having an island portion having a minimum diameter of 100 nm or more, or there is a sea-island structure having one or two or more island portions, and the total area of the island portions is 5% or less of the cross-sectional area of the fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to fibers and methods for manufacturing them, as well as fiber structures and methods for manufacturing them. Background Technology

[0002] In recent years, with the increasing use of fiber structures (non-woven fabrics, woven fabrics, woven fabrics, etc.) such as disposable masks, environmental pollution caused by microfibers flowing into the ocean has become obvious. Therefore, non-woven fabrics using plant-derived polylactic acid resins (abbreviated as PLA resins) have been proposed (for example, Patent Document 1).

[0003] However, PLA-based resins are difficult to compost at home, and there are also problems such as a lack of biodegradability in marine environments.

[0004] In contrast, poly(3-hydroxyalkanoate) resins (abbreviated as P3HA resins) have attracted attention because they can be composted at home and have excellent marine biodegradability. Nonwoven fabrics using P3HA resins have also been proposed (for example, Patent Document 2).

[0005] In addition, it has been proposed to use fibers containing polyhydroxyalkanoate copolymers and polylactic acid polymers in the manufacture of nonwoven fabrics (e.g., Patent Document 3).

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent No. 5356960

[0009] Patent Document 2: International Publication No. 2019 / 142920

[0010] Patent Document 3: Japanese Patent Publication No. 2004-532360 Summary of the Invention

[0011] The problem that the invention aims to solve

[0012] However, fiber structures using fibers containing poly(3-hydroxyalkanoate) resins suffer from the inherent problem of poly(3-hydroxyalkanoate) resins being prone to breakage.

[0013] Therefore, the objective of this invention is to provide a fiber containing a poly(3-hydroxyalkanoate) resin capable of producing a fibrous structure that is not easily broken, and a fibrous structure containing the fiber.

[0014] Problem Solving Methods

[0015] In order to solve the above problems, the inventors conducted in-depth research and found that by including poly(3-hydroxyalkanoate) resin and polylactic acid resin in a given ratio and constructing a fiber structure with a cross-section of a given structure, the fiber structure becomes less prone to breakage, thus completing the present invention.

[0016] Furthermore, it was discovered that by constructing a fiber structure from fibers made using a raw material composition comprising poly(3-hydroxyalkanoate) resin and polylactic acid resin in a given ratio, and wherein the melt mass flow rate of the polylactic acid resin is within a given range, the present invention was thus completed.

[0017] That is, the present invention relates to a fiber comprising a resin composition.

[0018] The above resin composition comprises a poly(3-hydroxyalkanoate) resin and a polylactic acid resin, wherein, relative to a total of 100 parts by weight of the poly(3-hydroxyalkanoate) resin and the polylactic acid resin, it comprises 50 to 99 parts by weight of the poly(3-hydroxyalkanoate) resin.

[0019] The cross-section of the aforementioned fibers does not have an island structure containing islands with a minimum diameter of 100 nm or more, or an island structure containing one or more of the aforementioned islands whose total area is less than 5% of the cross-sectional area of ​​the aforementioned fibers.

[0020] The average fiber diameter of the above fibers is less than 5 μm.

[0021] In addition, the present invention also relates to a method for manufacturing fibers, which is a method for manufacturing fibers by melt spinning, the method comprising:

[0022] A process of melting a raw material composition comprising poly(3-hydroxyalkanoate) resin and polylactic acid resin.

[0023] Relative to a total of 100 parts by weight of the above-mentioned poly(3-hydroxyalkanoate) resin and the above-mentioned polylactic acid resin, the above-mentioned raw material composition contains 50 to 99 parts by weight of the above-mentioned poly(3-hydroxyalkanoate) resin.

[0024] The melt flow rate of the above polylactic acid resin at 190℃ and 2.16kg load is 40~1500g / 10min.

[0025] The effects of the invention

[0026] According to the present invention, fibers containing poly(3-hydroxyalkanoate) resins that are capable of forming fibrous structures that are not easily broken, and fibrous structures containing the fibers can be provided. Attached Figure Description

[0027] Figure 1 This is a schematic diagram of a fiber manufacturing apparatus.

[0028] Figure 2 This is a three-dimensional schematic diagram of the nozzle.

[0029] Figure 3 This is a cross-sectional schematic diagram of the nozzle orifice and the conveyor belt.

[0030] Figure 4 This is a TEM image of the fiber cross-section of Example 3.

[0031] Figure 5 This is a TEM image of the fiber cross-section of Comparative Example 3.

[0032] Figure 6 This is a SEM image of the fiber structure in Example 3.

[0033] Figure 7 This is a SEM image of the fibrous structure in Comparative Example 3.

[0034] Figure 8 This is the DSC curve of the fiber from Example 3.

[0035] Figure 9 This is the DSC curve of the fiber in Comparative Example 3.

[0036] Figure 10 These are the results of biodegradation tests in seawater in the Examples, Comparative Examples, and Reference Examples.

[0037] Symbol Explanation

[0038] 1: Fiber manufacturing apparatus; 2: Hopper; 3: Extruder; 4: Gear pump; 5: Filter; 6: Mixer; 7: Nozzle; 7a: Nozzle orifice; 8: Collector; 8a: Conveyor belt; 8b: Roller; 9: Winding device.

[0039] A: Fibrous melt (raw material filaments), B: First fiber structure, C: Gas Detailed Implementation

[0040] Hereinafter, one embodiment of the present invention will be described with reference to the accompanying drawings.

[0041] <Fiber>

[0042] The fiber in this embodiment comprises a resin composition.

[0043] The above resin composition comprises a poly(3-hydroxyalkanoate) resin and a polylactic acid resin, and comprises 50 to 99 parts by weight of the poly(3-hydroxyalkanoate) resin relative to a total of 100 parts by weight of the poly(3-hydroxyalkanoate) resin and the polylactic acid resin.

[0044] The cross-section of the aforementioned fibers does not have an island structure containing islands with a minimum diameter of 100 nm or more, or an island structure containing one or more of the aforementioned islands and the total area of ​​the islands is less than 5% of the area of ​​the cross-section of the aforementioned fibers.

[0045] The average fiber diameter of the above fibers is less than 5 μm.

[0046] The above resin composition includes poly(3-hydroxyalkanoate) resins and polylactic acid resins.

[0047] (Poly(3-hydroxyalkanoate) resin)

[0048] The above-mentioned poly(3-hydroxyalkanoate) resin is a polyester containing 3-hydroxyalkanoic acid as a monomer.

[0049] That is, the above-mentioned poly(3-hydroxyalkanoate) resin is a resin containing 3-hydroxyalkanoic acid as a constituent unit.

[0050] In addition, the above-mentioned poly(3-hydroxyalkanoate) resins are biodegradable polymers.

[0051] It should be noted that "biodegradability" in this embodiment refers to the property of being able to be broken down into low-molecular-weight compounds by microorganisms in nature. Specifically, the presence or absence of biodegradability can be determined by tests suitable for various environments, such as ISO 14855 (compost) and ISO 14851 (activated sludge) under aerobic conditions, and ISO 14853 (aqueous phase) and ISO 15985 (solid phase) under anaerobic conditions. Furthermore, the decomposition ability of microorganisms in seawater can be evaluated by measuring biochemical oxygen demand (BOD).

[0052] The above-mentioned poly(3-hydroxyalkanoate) resin preferably comprises a copolymer having 3-hydroxybutyrate units.

[0053] In copolymers having 3-hydroxybutyrate units, monomer units other than 3-hydroxybutyrate units can be, for example, hydroxyalkyl ester units other than 3-hydroxybutyrate units.

[0054] Examples of hydroxyalkyl ester units other than the 3-hydroxybutyrate unit include: 3-hydroxyhexanoate, 3-hydroxyoctanoate, 3-hydroxyoctadecanoate, 3-hydroxyvalerate, 4-hydroxybutyrate, etc.

[0055] Examples of copolymers containing 3-hydroxybutyrate units include P3HB3HH, P3HB3HV, P3HB4HB, poly(3-hydroxybutyrate-copoly-3-hydroxyoctanoate), and poly(3-hydroxybutyrate-copoly-3-hydroxyoctadecanoate).

[0056] Here, P3HB3HH refers to poly(3-hydroxybutyrate-copolymer-3-hydroxyhexanoate).

[0057] P3HB3HV refers to poly(3-hydroxybutyrate-copolymer-3-hydroxyvalerate).

[0058] P3HB4HB refers to poly(3-hydroxybutyrate-copolymer-4-hydroxybutyrate).

[0059] The above-mentioned poly(3-hydroxyalkanoate) resin may contain only one copolymer having 3-hydroxybutyrate units, or it may contain two or more.

[0060] P3HB3HH is preferred as a copolymer having 3-hydroxybutyrate units.

[0061] Examples of poly(3-hydroxyalkyl ester) resins other than copolymers having 3-hydroxybutyrate units include P3HB, poly(3-hydroxyvalerate), and poly(3-hydroxyhexanoate).

[0062] Here, P3HB refers to poly(3-hydroxybutyrate) as a homopolymer.

[0063] It should be noted that P3HB has the function of promoting the crystallization of P3HB itself, as well as poly(3-hydroxyalkanoate) resins other than P3HB.

[0064] The content of the 3-hydroxybutyrate unit (3HB) in the above-mentioned poly(3-hydroxyalkanoate) resin is preferably 40 mol% or more and 98 mol% or less, more preferably 60 mol% or more and 97 mol% or less, further preferably 70 mol% or more and 96 mol% or less, and particularly preferably 80 mol% or more and 96 mol% or less.

[0065] By making the content of the 3-hydroxybutyrate unit in the above-mentioned poly(3-hydroxyalkanoate) resin at 40 mol% or more, the rigidity of the above-mentioned fiber is improved.

[0066] By keeping the content of the 3-hydroxybutyrate unit in the above-mentioned poly(3-hydroxyalkanoate) resin at 98 mol% or less, the fiber structure is less prone to breakage. Furthermore, by keeping the content of the 3-hydroxybutyrate unit in the above-mentioned poly(3-hydroxyalkanoate) resin at 92 mol% or less, the fiber structure is less prone to pilling and further less prone to breakage.

[0067] It should be noted that the content ratio of the 3-hydroxybutyrate unit in the above-mentioned poly(3-hydroxyalkanoate) resin refers to the content ratio of the 3-hydroxybutyrate unit in the whole of the above-mentioned poly(3-hydroxyalkanoate) resin contained in the above-mentioned fiber.

[0068] The proportion of 3-hydroxybutyrate units in the above-mentioned poly(3-hydroxyalkanoate) resin can be determined as follows.

[0069] First, 2 mL of a mixture of sulfuric acid and methanol (volume of sulfuric acid:volume of methanol = 15:85) and 2 mL of chloroform were added to 20 mg of the dried poly(3-hydroxyalkanoate) resin of the above resin composition. The resulting sample was sealed and heated at 100°C for 140 minutes under sealed conditions to obtain a first reaction solution containing methyl ester as a decomposition product of poly(3-hydroxyalkanoate) resin.

[0070] Then, the first reaction solution is cooled, and 1.5g of sodium bicarbonate is added to the cooled first reaction solution each time for neutralization. The reaction is allowed to proceed until the production of carbon dioxide stops, thus obtaining the second reaction solution.

[0071] Then, by thoroughly mixing the second reaction solution with 4 mL of diisopropyl ether, a mixture is obtained.

[0072] Next, the mixture is centrifuged to obtain the supernatant.

[0073] Then, the monomer unit composition of the above decomposition products in the supernatant was analyzed by capillary gas chromatography under the following conditions, thereby determining the content ratio of 3-hydroxybutyrate units in the poly(3-hydroxyalkanoate) resin.

[0074] Gas chromatograph: GC-17A manufactured by Shimadzu Corporation

[0075] Capillary column: NEUTRA BOND-1 manufactured by GL Sciences (column length: 25m, column inner diameter: 0.25mm, liquid film thickness: 0.4μm)

[0076] Carrier gas: He

[0077] Column inlet pressure: 100 kPa

[0078] Sample volume: 1 μL

[0079] Regarding temperature conditions, the temperature is increased at a rate of 8°C / min from 100 to 200°C, and further increased at a rate of 30°C / min from 200 to 290°C.

[0080] (Polylactic acid resin)

[0081] The aforementioned polylactic acid resin is a polyester with lactic acid as a constituent monomer.

[0082] Polylactic acid resins are preferably homopolymers of lactic acid, and may contain other monomers in addition to lactic acid.

[0083] The lactic acid constituting the polylactic acid resin can be either L-form or D-form, or may contain both. In the latter case, the proportion of D-form in the polylactic acid resin is preferably 1.0% or more and 99.0% or less, more preferably 1.5% or more and 98.5% or less, further preferably 2.0% or more and 98.0% or less, and particularly preferably 3.0% or more and 97.0% or less.

[0084] By making the ratio of D-body in the above-mentioned polylactic acid resin 1.0% or more and 99.0% or less, the melting point of the above-mentioned polylactic acid resin can be lowered, and it can be processed at a temperature at which poly(3-hydroxyalkanoate) resins are not easily decomposed.

[0085] Furthermore, by making the ratio of D-body in the above-mentioned polylactic acid resin 1.0% or more, biodegradability can be improved.

[0086] Polylactic acid resins can be any of poly(L-lactic acid) resins, poly(D-lactic acid) resins, and poly(DL-lactic acid) resins. Alternatively, they can be mixtures of these resins.

[0087] Other monomers that can be included in polylactic acid resins include aliphatic hydroxycarboxylic acids, aliphatic polyols, aliphatic polycarboxylic acids, and polyfunctional polysaccharides, in addition to lactic acid.

[0088] The polylactic acid (PLA) resin can be any type of PLA resin, including crystalline PLA resins and amorphous PLA resins. From the viewpoint of heat resistance, such as shrinkage upon heating, crystalline PLA resins are preferred. On the other hand, from the viewpoints of improving biodegradability and imparting heat-welding properties, amorphous PLA resins are preferred.

[0089] There are no particular limitations on the lactic acid raw material used in the manufacture of polylactic acid resins; L-lactic acid, D-lactic acid, DL-lactic acid, or mixtures thereof, L-lactide, D-lactide, mesolactide, or mixtures thereof can be used. Lactic acid obtained from renewable plant-derived raw materials such as starch through microbial fermentation can be appropriately utilized.

[0090] As a method for manufacturing polylactic acid resins, known methods such as dehydration condensation polymerization and ring-opening polymerization can be used, and there are no particular limitations.

[0091] From the viewpoint that the fibrous structure is not easily broken and that the resin composition contains a large amount of poly(3-hydroxyalkanoate) resin with excellent biodegradability (especially biodegradability in composting and marine decomposition), the resin composition contains 50 to 99 parts by weight of the poly(3-hydroxyalkanoate) resin, preferably 60 to 98 parts by weight, and more preferably 70 to 97 parts by weight, relative to a total of 100 parts by weight of the poly(3-hydroxyalkanoate) resin and the polylactic acid resin.

[0092] The aforementioned fibers are primarily composed of poly(3-hydroxyalkanoate) resins and polylactic acid resins. The combined percentage of poly(3-hydroxyalkanoate) resins and polylactic acid resins in the total fiber weight can be 50-100% by weight, preferably 70% by weight or more, more preferably 80% by weight or more, and even more preferably 90% by weight or more. It can also be 95% by weight or more, 98% by weight or more, or even 100% by weight.

[0093] (Other resins)

[0094] The above-described resin composition may include resins other than poly(3-hydroxyalkanoate) resins and polylactic acid resins, to a extent that does not impair the effects of the invention. Examples of such other resins include, for instance, aliphatic polyester resins such as polybutylene adipate, polybutylene succinate, and polycaprolactone; aliphatic aromatic polyester resins such as polybutylene adipate, polybutylene sebacic acid, and polybutylene azelaic acid. These other resins may include only one type or two or more types.

[0095] The content of the other resins mentioned above is not particularly limited, but is preferably 100 parts by weight or less, more preferably 50 parts by weight or less, and even more preferably 30 parts by weight or less, relative to 100 parts by weight of the total poly(3-hydroxyalkanoate) resin and polylactic acid resin. It can be 10 parts by weight or less, 5 parts by weight or less, or even 1 part by weight or less. The lower limit of the content of other resins is not particularly limited, and can be 0 parts by weight or more.

[0096] The above-described resin composition may contain additives that can be used with poly(3-hydroxyalkanoate) resins and polylactic acid resins, to a extent that does not impair the effects of the invention.

[0097] Examples of additives include: nucleating agents, lubricants, stabilizers (antioxidants, UV absorbers, etc.), colorants (dyes, pigments, etc.), plasticizers, inorganic fillers, organic fillers, and antistatic agents.

[0098] The above-mentioned resin composition preferably contains a crystallizing nucleating agent.

[0099] The aforementioned nucleating agent is a compound capable of promoting the crystallization of poly(3-hydroxyalkanoate) resins. Furthermore, the melting point of the aforementioned nucleating agent is higher than that of poly(3-hydroxyalkanoate) resins.

[0100] The above-described resin composition, by containing a nucleating agent, promotes the crystallization of the poly(3-hydroxyalkanoate) resin during fiber production, making it difficult for adjacent fibers to fuse together. As a result, a homogeneous fiber structure is easily obtained.

[0101] Examples of nucleating agents for the aforementioned crystallization include sugar alcohols such as pentaerythritol, galactitol, and mannitol; orotic acid, aspartame, cyanuric acid, glycine, zinc phenylphosphonate, and boron nitride. Among these, sugar alcohols are preferred, and pentaerythritol is particularly preferred, considering their particularly excellent effect on promoting the crystallization of poly(3-hydroxyalkanoates).

[0102] It should be noted that P3HB, as the aforementioned poly(3-hydroxyalkanoate) resin, can also be used as a crystallization nucleating agent.

[0103] They can be used individually or in combination of two or more.

[0104] Relative to 100 parts by weight of poly(3-hydroxyalkanoate) resin, the above resin composition preferably contains 0.1 parts by weight or more, more preferably 0.3 parts by weight or more, and even more preferably 0.5 parts by weight or more of a crystallizing nucleating agent.

[0105] By including more than 0.1 parts by weight of a crystallizing nucleating agent per 100 parts by weight of the poly(3-hydroxyalkanoate) resin, it has the advantage of more easily promoting the crystallization of the poly(3-hydroxyalkanoate) resin when making fibers.

[0106] In addition, relative to 100 parts by weight of poly(3-hydroxyalkanoate) resin, the above resin composition preferably contains 2.5 parts by weight or less, more preferably 2.0 parts by weight or less of a crystallizing nucleating agent.

[0107] By containing 2.5 parts by weight or less of a crystallizing nucleating agent relative to 100 parts by weight of the above resin composition, it is advantageous to easily obtain fibers.

[0108] It should be noted that P3HB is a poly(3-hydroxyalkanoate) resin and can also function as a crystallizing nucleating agent. Therefore, when the resin composition contains P3HB, the amount of P3HB is included in both the amount of the poly(3-hydroxyalkanoate) resin and the amount of the crystallizing nucleating agent.

[0109] The above-mentioned resin composition may contain the above-mentioned lubricant.

[0110] By incorporating lubricant into the fibers during manufacturing, the fibers become highly lubricated, which helps to prevent the fibers from fusing together.

[0111] On the other hand, when the above-mentioned resin composition does not contain lubricant, or contains only a trace amount of lubricant, it has advantages such as improved adhesion of fibers and fiber structures, and easier processing in the manufacturing process.

[0112] Whether or not lubricant is added, and the amount added, can be appropriately determined according to the intended use of the fiber.

[0113] Examples of such lubricants include compounds having amide bonds.

[0114] The compounds containing amide bonds mentioned above preferably include those selected from laurylamide, myristamide, stearamide, and styrax. One or more of acid amide and erucamide.

[0115] The lubricant content in the resin composition is preferably 0.2 parts by weight or more, more preferably 0.3 parts by weight or more, and even more preferably 0.5 parts by weight or more, relative to 100 parts by weight of the poly(3-hydroxyalkanoate) resin. By making the lubricant content in the resin composition 0.2 parts by weight or more relative to 100 parts by weight of the poly(3-hydroxyalkanoate) resin, it has the advantage of being able to further suppress the welding between fibers when manufacturing fibers.

[0116] On the other hand, when the content of lubricant in the resin composition is 0 parts by weight or more and less than 0.2 parts by weight relative to 100 parts by weight of the above-mentioned poly(3-hydroxyalkanoate) resin, it has the advantages of improved adhesion of fibers and fiber structures and easier processing in the manufacturing process.

[0117] Furthermore, the lubricant content in the resin composition is preferably 10 parts by weight or less, more preferably 5 parts by weight or less, further preferably 3 parts by weight or less, and most preferably 2 parts by weight or less, relative to 100 parts by weight of the poly(3-hydroxyalkanoate) resin. By making the lubricant content in the resin composition 10 parts by weight or less relative to 100 parts by weight of the poly(3-hydroxyalkanoate) resin, it has the advantage of being able to suppress the seepage of lubricant on the surface of the fiber.

[0118] The melt mass flow rate (hereinafter also referred to as "MFR" or "MFR(190°C, 2.16kg)") of the above resin composition at 190°C and 2.16kg load is preferably 20~1500g / 10min, more preferably 30~1400g / 10min, further preferably 50~1300g / 10min, particularly preferably 100~1200g / 10min, and most preferably 300~1000g / 10min.

[0119] By setting the MFR (190°C, 2.16 kg) of the above resin composition to 20~1500 g / 10 min, the fibers of this embodiment can be easily manufactured.

[0120] By making the MFR (190°C, 2.16 kg) of the above resin composition less than 1500 g / 10 min, the strength and elongation of the fiber are improved.

[0121] By setting the MFR (190°C, 2.16 kg) of the above resin composition to 20 g / 10 min or more, the tension applied to the fibrous melt during stretching (described later) can be suppressed, making it easier to obtain finer fibers. As a result, the capture efficiency of particles based on the fiber structure can be easily improved.

[0122] In this embodiment, for the melt mass flow rate (MFR) at 190°C and 2.16 kg load, the melt volumetric flow rate (MVR) of the object is determined by Method B of ASTM-D1238 (ISO1133-1, JIS K7210-1:2011), and the melt mass flow rate (MFR) of the object is determined based on the melt volumetric flow rate (MVR) and density of the object.

[0123] As a measuring device, a melt flow rate testing machine (G-02, manufactured by Toyo Seiki Co., Ltd.) can be used.

[0124] After heating 3-8g of the object at 190°C for 4 minutes, a load of 2.16kg was applied to the heated object, and the melt volumetric flow rate (MVR) of the object was determined.

[0125] The weight-average molecular weight of the above-mentioned resin composition is preferably 50,000 to 350,000, more preferably 70,000 to 300,000, further preferably 80,000 to 250,000 (e.g., 80,000 to 150,000), and particularly preferably 100,000 to 200,000.

[0126] By setting the weight-average molecular weight of the above-described resin composition to 50,000 to 350,000, the fibers of this embodiment can be easily manufactured.

[0127] By making the weight-average molecular weight of the above resin composition 50,000 or more, the strength and elongation of the fiber are improved.

[0128] By setting the weight-average molecular weight of the above resin composition to 350,000 or less, the tension applied to the fibrous melt during stretching can be reduced, making it easier to obtain finer fibers. As a result, the capture efficiency of particles based on the fiber structure can be easily improved.

[0129] It should be noted that, in this embodiment, the weight-average molecular weight (Mw) refers to the molecular weight determined by gel permeation chromatography (GPC) using chloroform eluent, based on the molecular weight distribution of polystyrene. As for the chromatographic column in this GPC, any column suitable for determining the aforementioned molecular weight can be used.

[0130] For example, the column temperature can be set to 40°C, and 10 μl of a solution obtained by dissolving 3 mg of the target substance in 2 ml of chloroform (HPLC grade) can be injected. The flow rate of the chloroform eluent (mobile phase) can be set to 1.0 ml / min, and the weight-average molecular weight (Mw) can be calculated. As the GPC apparatus, a Shimadzu 20A manufactured by Shimadzu Corporation can be used; as the column, a GPCK-806M (Showa Denko Corporation) can be used; and as the detector, an RI detector can be used.

[0131] The proportion of the above-mentioned resin composition in the above-mentioned fiber can be 50 to 100% by weight, preferably 70% by weight or more, more preferably 80% by weight or more, and even more preferably 90% by weight or more. It can be 95% by weight or more, or 98% by weight or more, or even 100% by weight.

[0132] The aforementioned fibers do not have an island structure in their cross-section that includes islands with a minimum diameter of 100 nm or more, or an island structure that includes one or more of the aforementioned islands and the total area of ​​the aforementioned islands is less than 5% of the area of ​​the cross-section of the aforementioned fibers.

[0133] The total area of ​​the aforementioned island portion is preferably 3% or less of the cross-sectional area of ​​the aforementioned fiber, more preferably 2% or less of the cross-sectional area of ​​the aforementioned fiber, and even more preferably 1% or less of the cross-sectional area of ​​the aforementioned fiber.

[0134] The fibers described above can form either non-island structures or co-continuous structures.

[0135] By making the above-mentioned fibers have an island structure in the cross section that does not have islands with a minimum diameter of 100 nm or more, or have an island structure that includes one or more of the above-mentioned islands and the total area of ​​the above-mentioned islands is less than 5% of the area of ​​the cross section of the above-mentioned fibers, the fiber structure is not easy to break.

[0136] It should be noted that the islands mentioned above refer to islands composed solely of P3HA-based or PLA-based resins; the island areas of other resins, additives, etc., are not included in the total area of ​​the islands mentioned above.

[0137] The ratio of the total area of ​​the islands in the cross-section of the fiber to the area of ​​the cross-section of the fiber can be calculated as follows.

[0138] First, a curable resin is impregnated into the fiber, or a fibrous structure containing the fiber, and then cured. The fiber is then cut to produce an ultrathin section. This cutting can be performed using an ultrathin microtome (FC6, manufactured by Leica Microsystems Co., Ltd.).

[0139] Next, the ultrathin sections were stained with RuO4, and images of the fiber cross-section were captured using a transmission electron microscope (e.g., Hitachi High-Tech Corporation H-7650) at an accelerating voltage of 100V. The magnification was set to 10,000x or 40,000x depending on the size of the fiber cross-section.

[0140] Then, using image analysis software (e.g., Win ROOF manufactured by Mitani Corporation), the proportion of the area of ​​islands (with a minimum diameter of 100 nm or more) consisting only of P3HA-based or PLA-based resins in the fiber cross-section is calculated.

[0141] It should be noted that, after determining the above proportions from the fiber structure, the cross-sectional areas of three or more fibers can be randomly selected from the captured image to calculate the proportion of the area of ​​islands (with a minimum diameter of 100 nm or more) composed solely of P3HA or PLA resin in the fiber cross-section.

[0142] The minimum diameter is the shortest line segment that passes through the midpoint of the line segment that determines the maximum diameter.

[0143] In the aforementioned fibers, the extrapolated glass transition onset temperature (T) derived from the polylactic acid resin component... ig (PLA) and the glass transition temperature at the midpoint (T) mg The temperature difference between the (PLA) and the temperature is preferably 2.0°C or higher, more preferably 2.3 to 12.0°C, even more preferably 2.5 to 10.0°C, and particularly preferably 2.7 to 9.0°C.

[0144] Extrapolated glass transition onset temperature (T) ig (PLA) and the glass transition temperature at the midpoint (T) mg The difference (PLA) refers to the difference in the glass transition temperature at the midpoint (T). mg (PLA) minus the extrapolated glass transition onset temperature (T) ig (PLA)) and the value (T) obtained mg (PLA)-T ig (PLA)).

[0145] Here, it is known that in a mixture of polylactic acid resin and other resin components, if the glass transition peak of the DSC curve originating from the polylactic acid resin component becomes broad, it indicates that either the polylactic acid resin or the other component is mixed in a micro-dispersed state with the other component.

[0146] By making the difference between the extrapolated glass transition start temperature and the intermediate glass transition temperature greater than 4.0°C, the peak of the DSC curve of the glass transition originating from the polylactic acid resin component becomes broader. In the fiber, it becomes a state in which either the polylactic acid resin or the poly(3-hydroxyalkanoate) resin is further mixed in a micro-dispersed state with the other, making the fiber structure less prone to breakage.

[0147] Extrapolated glass transition onset temperature (T) derived from polylactic acid resin components ig (PLA) and the glass transition temperature at the midpoint (T) mg (PLA) can be obtained as follows.

[0148] That is, based on JIS K7121-1987 "Method for Determination of Transition Temperature of Plastics", the fiber used as the object was measured under the conditions of 5~10mg sample amount, measurement temperature range: -30℃~200℃, and heating rate: 20℃ / min. DSC curves were obtained, and the extrapolated glass transition onset temperature (T0) derived from the polylactic acid resin component could be calculated using analytical software (TRIOS). ig (PLA)) and the glass transition temperature at the midpoint (T) mg (PLA)).

[0149] As the measuring device, a differential scanning calorimeter (DSC25, manufactured by TA Instruments) can be used.

[0150] The average fiber diameter of the above-mentioned fibers is 5 μm or less, preferably 5.0 μm or less, more preferably 4.9 μm or less, and even more preferably 4.8 μm or less.

[0151] In addition, the average fiber diameter of the above-mentioned fibers is preferably 0.5 μm or more, more preferably 0.8 μm or more, further preferably 1.0 μm or more, and particularly preferably 1.5 μm or more.

[0152] The coefficient of variation of the fiber diameter of the aforementioned fibers is preferably 0.30 or less, more preferably 0.27 or less, even more preferably 0.25 or less, and particularly preferably 0.20 or less. Furthermore, the coefficient of variation of the fiber diameter of the fibers in the aforementioned fiber structure is, for example, 0.05 or more.

[0153] By making the average fiber diameter of the aforementioned fibers less than 5 μm, the stiffness of the fibers can be reduced. As a result, when fabricating fiber structures, the texture (e.g., skin feel, hand feel, etc.) is improved. In addition, when fabricating fiber structures, the particle trapping efficiency is improved.

[0154] By making the average fiber diameter of the above-mentioned fibers 0.5 μm or more, in addition to improving the strength and elongation of the fibers and fiber structures, productivity is improved.

[0155] By making the coefficient of variation of the fiber diameter of the above-mentioned fibers less than 0.30, when the fiber structure is made, it becomes a fiber structure with less deviation in fiber diameter and more homogeneous, and the particle capture efficiency based on the fiber structure is further improved.

[0156] In the aforementioned fibers, as either polylactic acid resin or poly(3-hydroxyalkanoate) resin is mixed in a micro-dispersed state with the other, the coefficient of variation of the fiber diameter of the aforementioned fibers becomes a smaller value, and when the fiber structure is made, the particle capture efficiency is further improved.

[0157] It should be noted that the average value and variation coefficient of the fiber diameter of the above fibers can be calculated as follows.

[0158] When the fiber is a monofilament, firstly, at intervals of 10 cm or more relative to the fiber axis, the diameter (width) is measured at 20 or more randomly selected locations. For example, a scanning electron microscope can be used to measure the diameter (width).

[0159] Next, based on the arithmetic mean and standard deviation of all measured diameters (widths), calculate the above average (arithmetic mean) and coefficient of variation (=standard deviation / arithmetic mean).

[0160] When the aforementioned fibers are multifilaments, firstly, the diameter (width) of at least 100 randomly selected individual fibers is measured. For example, a scanning electron microscope can be used to measure the diameter (width).

[0161] Next, based on the arithmetic mean and standard deviation of all measured diameters (widths), calculate the above average (arithmetic mean) and coefficient of variation (=standard deviation / arithmetic mean).

[0162] In addition, in this embodiment, "fiber diameter of fiber" refers to "fiber diameter of a single fiber of fiber".

[0163] <Fiber Structure>

[0164] The fiber structure of this embodiment includes the fibers described above.

[0165] In this embodiment, the fibrous structure is preferably sheet-like.

[0166] Examples of such fibrous structures include: raw materials (non-woven fabrics, woven fabrics, braided fabrics, etc.).

[0167] Examples of nonwoven fabrics mentioned above include: chemically bonded nonwoven fabrics, thermally bonded nonwoven fabrics, needle-punched nonwoven fabrics, water-punched nonwoven fabrics, needle-jointed nonwoven fabrics, air-laid nonwoven fabrics, spunlace nonwoven fabrics, spunbond nonwoven fabrics, meltblown nonwoven fabrics, flash-spun nonwoven fabrics, electrospun nonwoven fabrics, and papermaking.

[0168] The aforementioned nonwoven fabric is preferably a direct-spun nonwoven fabric.

[0169] The aforementioned direct-spun nonwoven fabric refers to "a nonwoven fabric obtained by interlacing raw material filaments obtained through melt spinning, directly forming a sheet, and then solidifying the raw material filaments." It should be noted that "interlacing raw material filaments and directly forming a sheet" means "interlacing the raw material filaments to form a sheet before the raw material filaments solidify."

[0170] Examples of direct-spun nonwoven fabrics include meltblown nonwoven fabrics, spunbond nonwoven fabrics, flash-spun nonwoven fabrics, and electrospun nonwoven fabrics.

[0171] It should be noted that the above-mentioned meltblown nonwoven fabric also includes the concept of nonwoven fabric obtained through the Spunblown (registered trademark) law.

[0172] The fiber structure in this embodiment is more preferably meltblown nonwoven fabric or spunbond nonwoven fabric, and even more preferably meltblown nonwoven fabric.

[0173] The preferred unit area weight of the fiber structure in this embodiment is 10~150 g / m². 2 More preferably, it is 15~100g / m 2 A further preferred value is 20~80g / m 2 The preferred concentration is 20~60g / m³. 2 .

[0174] By making the unit area weight of the fiber structure in this embodiment 10 g / m² 2 In addition, the strength and elongation are improved, and the capture efficiency of particles (e.g., particles attached to blood cells, pollen, coffee powder, tea leaves, viruses, etc.) is improved.

[0175] Furthermore, by making the unit area weight of the fiber structure in this embodiment 150 g / m² 2 The following indicates that the permeability to liquids (such as water) or air increases.

[0176] It should be noted that the weight per unit area of ​​the fiber structure in this embodiment can be calculated as follows.

[0177] First, a test piece is obtained from the fiber structure of this embodiment.

[0178] The size of the test piece can be set to, for example, 100mm×100mm, 200mm×200mm, etc.

[0179] Next, the weight of the test piece was determined using an electronic balance.

[0180] Then, divide the weight of the test piece by its area to calculate the weight per unit area.

[0181] In addition, the thickness of the fiber structure in this embodiment is preferably 0.05 to 0.80 mm, more preferably 0.08 to 0.60 mm, even more preferably 0.10 to 0.50 mm, and particularly preferably 0.10 to 0.40 mm.

[0182] By setting the thickness of the fiber structure in this embodiment to 0.05~0.80 mm, a homogeneous fiber structure can be easily obtained during its fabrication.

[0183] Furthermore, by making the thickness of the fiber structure in this embodiment 0.05 mm or more, the strength and elongation of the fiber structure are increased, and the particle capture efficiency based on the fiber structure is further improved.

[0184] Furthermore, by making the thickness of the fiber structure in this embodiment less than 0.80 mm, the liquid permeability (water permeability, etc.) or air permeability of the fiber structure can be improved.

[0185] It should be noted that, for the thickness of the fiber structure in this embodiment, the arithmetic mean of the thickness of the fiber structure can be obtained by measuring the thickness at three or more locations using a thickness gauge.

[0186] As a thickness gauge, examples include "PEACOCK" manufactured by Ozaki Seisakusho Co., Ltd.

[0187] The average fiber diameter of the fibers in the above-mentioned fiber structure is preferably 5 μm or less, more preferably 5.0 μm or less, even more preferably 4.9 μm or less, and even more preferably 4.8 μm or less.

[0188] Furthermore, the average fiber diameter of the fibers in the aforementioned fiber structure is preferably 0.5 μm or more, more preferably 0.8 μm or more, even more preferably 1.0 μm or more, and even more preferably 1.5 μm or more.

[0189] The coefficient of variation of the fiber diameter in the aforementioned fiber structure is preferably 0.30 or less, more preferably 0.27 or less, even more preferably 0.25 or less, and particularly preferably 0.20 or less. Furthermore, the coefficient of variation of the fiber diameter in the aforementioned fiber structure is, for example, 0.05 or more.

[0190] By making the average fiber diameter of the fibers in the above-mentioned fiber structure less than 5 μm, the stiffness of the fibers can be reduced, which not only improves the texture of the fiber structure (e.g., skin feel, hand feel, etc.) but also increases the particle capture efficiency.

[0191] By making the average fiber diameter of the fibers in the above-mentioned fiber structure 0.5 μm or more, the strength and elongation of the fiber structure are improved.

[0192] By making the variation coefficient of the fiber diameter in the above-mentioned fiber structure less than 0.30, the fiber structure becomes a fiber structure with less deviation in fiber diameter and is homogeneous, and the capture efficiency of particles based on the fiber structure is further improved.

[0193] In the fiber structure described above, as the fibers are mixed in a micro-dispersed state between polylactic acid resin and poly(3-hydroxyalkanoate) resin, the coefficient of variation of the fiber diameter in the fiber structure becomes smaller, and the particle capture efficiency based on the fiber structure is further improved.

[0194] It should be noted that the average value and variation coefficient of the fiber diameter in the above-mentioned fiber structure can be calculated as follows.

[0195] First, test pieces are obtained from fibrous structures.

[0196] Next, at least five photographs (1700x magnification) were taken on the surface of the test piece using a scanning electron microscope.

[0197] Then, the diameter (width) of more than 20 randomly selected fibers was measured from one photograph.

[0198] Next, the arithmetic mean and coefficient of variation (= standard deviation / arithmetic mean) are calculated based on the measured diameter (width) values ​​of all fibers.

[0199] The proportion of the aforementioned fibers in the total amount of the aforementioned fiber structure can be 50 to 100% by weight, preferably 70% by weight or more, more preferably 80% by weight or more, and even more preferably 90% by weight or more. It can be 95% by weight or more, or 98% by weight or more, or even 100% by weight.

[0200] The fiber structure of this embodiment can be suitably used as a substrate for various products (e.g., masks, filters, disposable diapers, sanitary napkins, adhesive bandages, patches, bags, gloves, clothing, etc.). It should be noted that the substrate concept includes reinforcing materials.

[0201] Examples of such filters include removal filters (e.g., filters for face masks) that remove particles (e.g., particles with attached viruses, pollen, etc.), blood filters that capture blood cells, and filters for beverage extraction (e.g., filters for coffee dripping, tea bags, etc.).

[0202] <Methods for manufacturing fibers and fiber structures>

[0203] The fiber manufacturing method of this embodiment can manufacture the above-mentioned fibers.

[0204] The fiber manufacturing method of this embodiment is a fiber manufacturing method using melt spinning.

[0205] In addition, the fiber manufacturing method of this embodiment includes a step (A) of melting a raw material composition comprising a poly(3-hydroxyalkanoate) resin and a polylactic acid resin.

[0206] The raw material composition comprises 50 to 99 parts by weight of the poly(3-hydroxyalkanoate) resin and the polylactic acid resin, relative to a total of 100 parts by weight of the above-mentioned poly(3-hydroxyalkanoate) resin and the above-mentioned polylactic acid resin.

[0207] The melt flow rate of the above polylactic acid resin at 190°C is 40~1500g / 10min.

[0208] In the fiber manufacturing method of this embodiment, a nozzle having a nozzle hole is used to manufacture fibers.

[0209] The fiber manufacturing method of this embodiment includes a step (A) of obtaining a melt by melting a raw material composition comprising a poly(3-hydroxyalkanoate) resin and a polylactic acid resin; and a step (B) of obtaining fibers from the melt.

[0210] In the fiber structure manufacturing method of this embodiment, a fiber structure containing the above-described fibers is manufactured by the fiber manufacturing method described above.

[0211] Examples of melt spinning methods include meltblowing, spunbonding, flash spinning, and electrospinning.

[0212] The melt spinning method described above is preferably the melt-blowing method or the spunbond method.

[0213] The above-mentioned raw material composition includes poly(3-hydroxyalkanoate) resin and polylactic acid resin.

[0214] The raw material composition comprises 50 to 99 parts by weight, preferably 60 to 98 parts by weight, and more preferably 70 to 97 parts by weight, of the poly(3-hydroxyalkanoate) resin, relative to a total of 100 parts by weight of the poly(3-hydroxyalkanoate) resin and the polylactic acid resin.

[0215] The above-mentioned raw material composition is a raw material composition mainly composed of poly(3-hydroxyalkanoate) resin and polylactic acid resin. The total proportion of poly(3-hydroxyalkanoate) resin and polylactic acid resin in the total amount of the raw material composition can be 50% by weight or more, preferably 70% by weight or more, more preferably 80% by weight or more, and even more preferably 90% by weight or more. It can be 95% by weight or more, or 98% by weight or more.

[0216] The MFR (190°C, 2.16 kg) of the above-mentioned polylactic acid resin is 40~1500 g / 10 min, preferably 50~1300 g / 10 min, more preferably 60~1200 g / 10 min, further preferably 80~1000 g / 10 min, and particularly preferably 100~800 g / 10 min.

[0217] By making the MFR (190°C, 2.16kg) of the above-mentioned polylactic acid resin 40g / 10min or more, the fiber becomes a state in which either polylactic acid resin or poly(3-hydroxyalkanoate) resin is further mixed in a micro-dispersed state with the other, making the fiber structure less prone to breakage.

[0218] By reducing the MFR (190°C, 2.16 kg) of the polylactic acid resin to below 1500 g / 10 min, the strength and elongation of the fiber are improved.

[0219] The MFR (210°C, 2.16 kg) of the above-mentioned polylactic acid resin is preferably more than 80 g / 10 min and less than 2000 g / 10 min, more preferably 90 to 1800 g / 10 min, even more preferably 90 to 1500 g / 10 min (e.g., 150 to 1500 g / 10 min), even more preferably 100 to 1200 g / 10 min, and particularly preferably 150 to 1000 g / 10 min.

[0220] By making the MFR (210°C, 2.16kg) of the above-mentioned polylactic acid resin exceed 80g / 10min, the polylactic acid resin and poly(3-hydroxyalkanoate) resin are further mixed in a micro-dispersed state in the fiber, making the fiber structure less prone to breakage.

[0221] By reducing the MFR (210℃, 2.16kg) of the polylactic acid resin to below 2000g / 10min, the strength and elongation of the fiber are improved.

[0222] It should be noted that the MFR (210℃, 2.16kg) can be measured by changing the heating temperature from 190℃ to 210℃ in the above-mentioned method for measuring MFR (190℃, 2.16kg).

[0223] The weight-average molecular weight of the polylactic acid resin is preferably 20,000 to 120,000, more preferably 40,000 to 110,000, even more preferably 40,000 to 100,000, and particularly preferably 50,000 to 100,000.

[0224] By increasing the weight-average molecular weight of the polylactic acid resin to over 20,000, the strength and elongation of the fiber are improved.

[0225] By making the weight-average molecular weight of the polylactic acid resin below 120,000, it becomes a state in which either polylactic acid resin or poly(3-hydroxyalkanoate) resin is further mixed in a micro-dispersed state with the other in the fiber, making the fiber structure less prone to breakage.

[0226] The MFR (190°C, 2.16 kg) of the above-mentioned raw material composition is preferably 1~1500 g / 10 min, more preferably 5~1200 g / 10 min, further preferably 10~1000 g / 10 min, particularly preferably 20~800 g / 10 min, even more preferably 50~500 g / 10 min, even more preferably 80~400 g / 10 min, and most preferably 90~300 g / 10 min.

[0227] By setting the MFR (190°C, 2.16 kg) of the above-mentioned raw material composition to 1~1500 g / 10 min, the fiber of this embodiment can be easily manufactured.

[0228] By making the MFR (190°C, 2.16kg) of the above raw material composition below 1500g / 10min, the strength and elongation of the fiber structure are further improved.

[0229] By achieving a minimum molecular weight ratio (MFR, 190°C, 2.16 kg) of 1 g / 10 min for the above-mentioned raw material composition, the tension applied to the fibrous melt during stretching can be reduced, making it easier to obtain fibers with a finer diameter. As a result, the particle trapping efficiency based on the fiber structure is further improved.

[0230] The weight-average molecular weight of the above-mentioned raw material composition is preferably 100,000 to 550,000, more preferably 110,000 to 450,000, further preferably 120,000 to 350,000, and particularly preferably 150,000 to 250,000.

[0231] By making the weight-average molecular weight of the above-mentioned raw material composition 100,000 to 550,000, the fiber of this embodiment can be easily manufactured.

[0232] By making the weight-average molecular weight of the above raw material composition 100,000 or more, the strength and elongation of the fiber structure are further improved.

[0233] By setting the weight-average molecular weight of the above-mentioned raw material composition to below 550,000, the tension applied to the fibrous melt during stretching can be reduced, making it easier to reduce the fiber diameter. As a result, the particle trapping efficiency based on the fiber structure is further improved.

[0234] Hereinafter, the method for manufacturing fibers and fiber structures according to this embodiment will be described using a melt-blowing method as a specific example.

[0235] It should be noted that the above-mentioned meltblown method also includes the concept of the Spunblown (registered trademark) law.

[0236] In the fiber manufacturing method and fiber structure manufacturing method of this embodiment, a fiber manufacturing apparatus is used to obtain a fiber structure from the above-mentioned raw material composition.

[0237] like Figure 1 As shown, the fiber manufacturing apparatus 1 includes: an extruder 3 that obtains a molten material by melting a raw material composition; a hopper 2 that supplies the raw material composition to the extruder 3; a mixing machine 6 that mixes the molten material; a nozzle 7 that ejects the mixed molten material in a fibrous form; a collecting machine 8 that obtains a first fiber structure B by collecting the fibrous molten material and cooling it; and a winding device 9 that winds up the first fiber structure B.

[0238] Additionally, the fiber manufacturing apparatus 1 can supply the molten material to the gear pump 4 of the mixer 6 as needed.

[0239] By equipping the fiber manufacturing apparatus 1 with a gear pump 4, it is possible to suppress fluctuations in the amount of melt supplied to the mixer 6.

[0240] Furthermore, if necessary, the fiber manufacturing apparatus 1 may be equipped with a filter 5 on the upstream side of the mixer 6 to remove foreign matter from the melt.

[0241] In the above process (A), the raw material composition is fed to the extruder 3 via the hopper 2, causing the raw material composition to melt, thereby obtaining a melt.

[0242] The raw material composition supplied to the extruder 3 is preferably in solid form, more preferably in granular form.

[0243] Furthermore, from the viewpoint of suppressing resin hydrolysis in the raw material composition and suppressing oxidative deterioration of the resin in the raw material composition, it is preferable to heat and dry the raw material composition supplied to the extruder 3.

[0244] The moisture content in the raw material composition supplied to the extruder 3 is preferably 1000 ppm or less, more preferably 500 ppm or less, and even more preferably 300 ppm or less.

[0245] When drying the raw material composition, it is preferable to remove oxygen from the atmosphere, or to remove oxygen from the raw material composition itself. It is preferable to set the drying atmosphere to an atmosphere of an inert gas (e.g., nitrogen).

[0246] In the above process (A), the raw material composition can be dried before being fed to the hopper 2. Alternatively, the hopper 2 can be configured as a hopper-type dryer, and the drying of the raw material composition can be carried out through the hopper 2.

[0247] Examples of extruders 3 mentioned above include: single-screw extruders, co-rotating twin-screw extruders, co-rotating non-rotating twin-screw extruders, counter-rotating non-rotating twin-screw extruders, and multi-screw extruders.

[0248] From the viewpoints of minimizing resin retention within the extruder and thus easily suppressing thermal degradation of the raw material composition during extrusion, and from the viewpoint of low equipment costs, a single-screw extruder is preferred as the aforementioned extruder 3.

[0249] In addition, in the above process (A), the molten material is supplied to the mixer 6 via the filter 5 by the gear pump 4, and the molten material is mixed by the mixer 6.

[0250] Examples of filters 5 mentioned above include: screens, pleated filters, and disc filters.

[0251] From the viewpoints of filtration accuracy, filtration area, pressure resistance, and the likelihood of clogging caused by foreign objects, the impeller-type filter is preferred as the filter 5 described above.

[0252] For example, sintered nonwoven fabric with metal fibers can be used as the filter material for filter 5.

[0253] In the above process (B), the molten material is ejected from nozzle 7 in a fibrous form.

[0254] The nozzle 7 mentioned above is a spinning die head.

[0255] exist Figure 2 In this process, the nozzle 7 has a plurality of nozzle holes 7a that eject the molten material in a fibrous manner. Furthermore, as... Figure 2 As shown, the nozzle 7 ejects multiple fibrous melts A (also known as "raw material filaments A").

[0256] It should be noted that the nozzle 7 described above may have only one nozzle hole 7a ("nozzle hole" is also simply referred to as "hole"). That is, the nozzle 7 described above may eject only one raw material filament A.

[0257] Multiple nozzle holes 7a open downwards.

[0258] The opening shape of the nozzle hole 7a is, for example, circular (including the concepts of circular, roughly circular, elliptical, and roughly elliptical).

[0259] The opening diameter of the nozzle orifice 7a can be appropriately selected according to the fiber diameter of the fiber structure.

[0260] The opening diameter of the nozzle orifice 7a is preferably 0.05 mm or more, more preferably 0.10 mm or more, and even more preferably 0.15 mm or more.

[0261] In addition, the opening diameter is preferably 1.0 mm or less, more preferably 0.5 mm or less, even more preferably 0.4 mm or less, and particularly preferably 0.3 mm or less.

[0262] The above-mentioned opening diameter (also known as "hole diameter") refers to the arithmetic mean of the above-mentioned opening diameters.

[0263] In the above-mentioned nozzle 7, multiple nozzle holes 7a are arranged in a row with intervals between them.

[0264] exist Figure 2 In the middle, multiple nozzle holes 7a are arranged in a row.

[0265] It should be noted that the number of nozzle orifices 7a can be two or more columns. In other words, the above-mentioned melt-blowing method can be the Spunblown (registered trademark) method.

[0266] The distance between adjacent nozzle holes 7a (hereinafter also referred to as "interval" or "hole spacing") is preferably 0.05 mm or more, more preferably 0.10 mm or more, and even more preferably 0.25 mm or more.

[0267] By making the distance (interval) between adjacent nozzle holes 7a greater than 0.05 mm, it is possible to suppress the fusion of adjacent fibers with each other, and as a result, the coefficient of variation of the fiber diameter can be reduced.

[0268] In addition, the distance (interval) between adjacent nozzle holes 7a is preferably 3.0 mm or less, more preferably 2.0 mm or less, and even more preferably 1.0 mm or less.

[0269] The distance between adjacent nozzle holes 7a can be equal or unequal, but from the perspective of easily manufacturing homogeneous fiber structures, equal distance is preferred.

[0270] The distance (interval) between adjacent nozzle orifices 7a refers to the arithmetic mean of the distances (intervals) between adjacent nozzle orifices 7a.

[0271] The aforementioned collector 8 has a collecting surface for collecting fibrous melt A.

[0272] The aforementioned collector 8 is a conveyor.

[0273] The conveyor described above includes a conveyor belt 8a having the aforementioned collecting surface and a plurality of rollers 8b that drive the conveyor belt 8a.

[0274] The aforementioned collection surface is positioned directly below the aforementioned nozzle orifice 7a.

[0275] The aforementioned conveyor belt 8a is breathable. Specifically, the conveyor belt 8a is formed of a mesh-like material. That is, the collecting surface is mesh-like.

[0276] It should be noted that the above-mentioned collecting machine 8 only needs to have a collecting section, and a collecting tube or a collecting net can be used instead of the above-mentioned conveyor.

[0277] The distance between the nozzle hole 7a and the collection surface (hereinafter also referred to as "DCD") is preferably 20 mm or more, more preferably 50 mm or more, and even more preferably 80 mm or more.

[0278] Furthermore, the distance (DCD) between the nozzle hole 7a and the conveyor belt 8a, which serves as the collection section, is preferably 300 mm or less, and more preferably 250 mm or less.

[0279] The distance (DCD) between the nozzle orifice 7a and the aforementioned collection surface refers to the arithmetic mean of the distances (DCD) between the nozzle orifice 7a and the aforementioned collection surface.

[0280] like Figure 3 As shown, the fiber manufacturing apparatus 1 is configured to stretch the fibrous melt A by blowing high-temperature gas C onto the fibrous melt A.

[0281] In the above process (B), high-temperature gas C is blown into the fibrous melt A, and the high-temperature gas C blown into the melt A passes through the mesh conveyor belt 8a.

[0282] In the above-described process (B), in order to allow the high-temperature gas C blown onto the melt A to pass through the mesh conveyor belt 8a, it is preferable to use a suction machine (not shown) to suction the high-temperature gas C. This easily prevents fiber rebound on the collecting surface of the mesh conveyor belt 8a, resulting in the easy formation of a first fiber structure B where the fibers are well fused together.

[0283] Then, in the above-described process (B), the stretched fibrous melt A is captured by conveyor belt 8a and cooled while being transported by conveyor belt 8a, thereby obtaining fibers. In addition, a first fiber structure containing these fibers is obtained.

[0284] The material constituting the mesh-like trapping surface is not particularly limited as long as it has heat resistance to the temperature conditions related to the manufacturing of the first fiber structure B, does not excessively fuse with the first fiber structure B, and can peel off the first fiber structure B.

[0285] Examples of gas C mentioned above include air and inert gases (such as nitrogen).

[0286] As a method for blowing high-temperature gas C, one example is heating gas C that has been pressurized by a compressor (not shown) using a heater (not shown).

[0287] The flow rate of the high-temperature gas C blown onto the fibrous melt A is preferably 500 NL / min or more, more preferably 1000 NL / min or more, and even more preferably 2000 NL / min or more.

[0288] In addition, the air volume of the high-temperature gas C blown onto the fibrous melt A is preferably 12,000 NL / min or less, more preferably 10,000 NL / min or less.

[0289] In the above process (B), in order to obtain a fiber structure with high crystallinity, the temperature and air volume of the high-temperature gas C are appropriately controlled.

[0290] In the above process (B), the first fiber structure B is transferred to the winding device 9 by the above conveyor belt 8a, and the first fiber structure B is wound into a roll by the winding device 9.

[0291] The manufacturing method of the fiber structure in this embodiment may include a step (C) of heating the first fiber structure B obtained in the above step (B) to obtain the second fiber structure.

[0292] It should be noted that when the manufacturing method of the fiber structure in this embodiment includes the above-described step (C), the second fiber structure becomes the above-described fiber structure. On the other hand, when the manufacturing method of the fiber structure in this embodiment does not include the above-described step (C), the first fiber structure becomes the above-described fiber structure.

[0293] The fiber structure manufacturing method of this embodiment, through the above-described process (C), makes the fiber structure less prone to breakage.

[0294] Furthermore, the fiber structure manufacturing method of this embodiment can improve the tensile elongation at the break point in the MD and CD directions of the fiber structure through the above-mentioned process (C).

[0295] Furthermore, the fiber structure manufacturing method of this embodiment, through the above-described process (C), partially fuses the fibers together, resulting in easy suppression of fuzzing of the fiber structure.

[0296] The preferred heating temperature range for the above process (C) is 80°C to 135°C.

[0297] The heating time in the above-mentioned process (C) is preferably 2 to 300 minutes, more preferably 5 to 100 minutes, and even more preferably 10 to 50 minutes within the preferred heating temperature range.

[0298] In the above process (C), by heating the first fiber structure within the preferred heating temperature range for more than 2 minutes, the tensile elongation at the break point in the CD and MD directions of the fiber structure can be improved.

[0299] It should be noted that the MD direction is the direction in which the fiber structure moves during manufacturing (Machine Direction). The CD direction is the direction perpendicular to the MD direction.

[0300] Furthermore, in the above-mentioned process (C), by heating the first fiber structure for 300 minutes or less within the preferred heating temperature range, the productivity of the second fiber structure is improved.

[0301] In the above process (C), the first fiber structure can be heated by a gas within the preferred heating temperature range.

[0302] Examples of such gases include air and inert gases (such as nitrogen).

[0303] As a method for heating the first fiber structure by means of a gas within the preferred heating temperature range, examples include heating the first fiber structure in a heating furnace by means of a gas within the preferred heating temperature range, and / or heating the first fiber structure by means of ...

[0304] In addition, in the above process (C), the first fiber structure can be heated within the preferred heating temperature range by clamping the first fiber structure with a pair of heating rollers.

[0305] In the above process (C), it is preferable to heat the first fiber structure in a non-contact manner within the preferred heating temperature range.

[0306] In the above process (C), when the first fiber structure is held and heated by a pair of heating rollers, there is a risk that the first fiber structure may melt and stick to the heating rollers.

[0307] In the above process (C), the first fiber structure is heated in a non-contact manner within the preferred heating temperature range, thereby having the advantage of suppressing the melting and adhesion between the first fiber structure and the heating roller.

[0308] As a method for heating the first fiber structure in a non-contact manner within the preferred heating temperature range described above, examples include heating the first fiber structure with a gas within the preferred heating temperature range described above.

[0309] In the above process (C), the first fiber structure can be heated while it is wound into a roll.

[0310] Alternatively, in the above-described process (C), the first fiber structure may not be wound into a roll, but rather formed into a sheet and heated. For example, the heating can be performed continuously while transporting the long strip of the first fiber structure.

[0311] In the above process (C), the second fiber structure is obtained by cooling the heated first fiber structure.

[0312] As a method for cooling the heated first fiber structure, one method is to allow the heated first fiber structure to cool naturally at room temperature and pressure. Alternatively, the heated first fiber structure can be forcibly cooled by blowing gas (e.g., gas at room temperature) into it.

[0313] It should be noted that the present invention is not limited to the embodiments described above. Furthermore, the present invention is not limited to the effects described above. In addition, various modifications can be made to the present invention without departing from its spirit.

[0314] The above description of the fiber manufacturing method and the fiber structure of this embodiment has been based on the example of obtaining fibers and fiber structures by melt-blowing, but various modifications can be made without departing from the spirit of the present invention.

[0315] For example, in the fiber manufacturing method and the fiber structure manufacturing method of this embodiment, the fiber and fiber structure can be manufactured by spunbonding, flash spinning or electrospinning.

[0316] In the fiber manufacturing method and the fiber structure manufacturing method of this embodiment, the above-mentioned nonwoven fabric is preferably manufactured by meltblowing or spunbonding.

[0317] In the above spunbond process, the above raw material composition is melted by heating to obtain the above melt, and the above raw material filament is obtained by ejecting the above melt from the above nozzle orifice.

[0318] Next, the raw material filament is stretched by blowing gas onto it.

[0319] It should be noted that in the above spunbond method, stretching rollers can be used to stretch the raw material filaments.

[0320] In step (B) of the spunbond process, the fibers are stretched using a suction device such as an ejector. When using an ejector, the spinning speed can be adjusted by changing the air traction pressure. By increasing the volume of blown air (increasing the air pressure), the spinning speed increases, and the fibers are further stretched.

[0321] In step (B), before the raw filaments extruded from the spinning nozzle in step (A) are drawn and refined, rectifying air can be supplied to the raw filaments using a device that provides quenching air or similar rectifying air. Rectifying air, also known as quenching air, has the function of stabilizing the flow of the raw filaments as a filament. Alternatively, the raw filaments as spinning filaments can be cooled using cooled gas. Preferably, the quenching air is released through a mesh or sieve and evenly supplied to the filament. For the filament, the rectifying air can be supplied from one or both sides of the material formed by the interlacing of filaments, or it can be supplied in a circumferential manner.

[0322] In the above-mentioned flash spinning method, the material of the above-mentioned raw material composition is mixed with a solvent under high temperature and high pressure to obtain a melt under high temperature and high pressure.

[0323] Next, the above-mentioned raw material filament is obtained by ejecting the molten material under high temperature and high pressure from the nozzle hole at normal temperature and pressure, and the obtained raw material filament is stretched.

[0324] Examples of solvents mentioned above include alcohols (e.g., methanol, ethanol, etc.) and acetone.

[0325] In the electrospinning method described above, the raw material composition is heated and melted by irradiating it with a laser while it is under a high voltage. As a result, the melt is obtained. Next, the melt is ejected from the nozzle orifice to obtain a raw material filament. Then, the raw material filament is stretched using electrostatic force.

[0326] [Public Projects]

[0327] The following items are disclosures of preferred embodiments.

[0328] [Project 1]

[0329] A fiber comprising a resin composition.

[0330] The above resin composition comprises a poly(3-hydroxyalkanoate) resin and a polylactic acid resin, wherein, relative to a total of 100 parts by weight of the poly(3-hydroxyalkanoate) resin and the polylactic acid resin, it comprises 50 to 99 parts by weight of the poly(3-hydroxyalkanoate) resin.

[0331] The cross-section of the aforementioned fibers does not have an island structure containing islands with a minimum diameter of 100 nm or more, or an island structure containing one or more of the aforementioned islands whose total area is less than 5% of the cross-sectional area of ​​the aforementioned fibers.

[0332] The average fiber diameter of the above fibers is less than 5 μm.

[0333] [Project 2]

[0334] According to the fiber described in Project 1, wherein,

[0335] The coefficient of variation for the fiber diameter of the above-mentioned fibers is less than 0.30.

[0336] [Project 3]

[0337] According to the fibers described in item 1 or 2, wherein,

[0338] In the aforementioned fibers, the difference between the extrapolated glass transition start temperature and the intermediate glass transition temperature derived from polylactic acid resin components is greater than 2.0°C.

[0339] [Project 4]

[0340] The fiber according to any one of items 1 to 3, wherein,

[0341] The melt flow rate of the above resin composition at 190°C and 2.16 kg load is 20~1500 g / 10 min.

[0342] [Project 5]

[0343] The fiber according to any one of items 1 to 4, wherein,

[0344] The above-mentioned poly(3-hydroxyalkanoate) resin is poly(3-hydroxybutyrate-copolymer-3-hydroxyhexanoate).

[0345] [Project 6]

[0346] A fibrous structure comprising the fibers described in any one of items 1 to 5.

[0347] [Project 7]

[0348] The fiber structure described in Project 6 is a spunbond nonwoven fabric or a meltblown nonwoven fabric.

[0349] [Project 8]

[0350] A method for manufacturing fibers, which is a method for manufacturing fibers by melt spinning, the method comprising:

[0351] A process of melting a raw material composition comprising poly(3-hydroxyalkanoate) resin and polylactic acid resin.

[0352] Relative to a total of 100 parts by weight of the above-mentioned poly(3-hydroxyalkanoate) resin and the above-mentioned polylactic acid resin, the above-mentioned raw material composition contains 50 to 99 parts by weight of the above-mentioned poly(3-hydroxyalkanoate) resin.

[0353] The melt flow rate of the above polylactic acid resin at 190℃ and 2.16kg load is 40~1500g / 10min.

[0354] [Project 9]

[0355] According to the fiber manufacturing method described in Project 8, wherein,

[0356] The weight-average molecular weight of the above-mentioned polylactic acid resins is 20,000 to 120,000.

[0357] [Project 10]

[0358] A method for manufacturing a fiber structure, the method comprising:

[0359] A fibrous structure comprising the aforementioned fibers is manufactured using the fiber manufacturing method described in item 8 or 9.

[0360] The above-mentioned melt spinning method is either melt-blowing or spunbonding.

[0361] Example

[0362] The present invention will now be described in more detail by way of examples. It should be noted that the present invention is not limited to these examples.

[0363] The following materials have been prepared.

[0364] (Poly(3-hydroxyalkanoate) resins (P3HA resins))

[0365] P3HB3HH (melting point: 145°C, MFR (190°C, 2.16 kg): 65 g / 10 min, content of 3-hydroxybutyrate unit (3HB unit): 94.9 mol%, content of 3-hydroxyhexanoate unit (3HH unit): 5.1 mol%, weight average molecular weight: 240,000) was prepared as a P3HA-based resin according to the method described in Example 1 of International Publication No. 2019 / 142845.

[0366] The melting point mentioned above refers to the peak temperature Tm of the crystallization melting peak in the DSC curve obtained by differential scanning calorimetry (DSC measurement). The DSC curve is obtained by accurately weighing approximately 5 mg of the resin being measured and heating it from 0 °C to 200 °C at a heating rate of 10 °C / min using a differential scanning calorimeter.

[0367] In addition, the MFR (190°C, 2.16 kg), the content of 3HB units, the content of 3HH units, and the weight-average molecular weight of poly(3-hydroxyalkanoate) resins were determined by the methods described above.

[0368] (Polylactic acid (PLA) based resins)

[0369] Using a highly accelerated life testing apparatus (ESPEC, EHS-222MD), the following PLA-based resins were hydrolyzed under high temperature and high humidity conditions (temperature: 105°C, humidity: 100%) for the following duration, and then dried overnight at 80°C, thereby obtaining the following PLA-1~6.

[0370] PLA-1 was prepared by hydrolyzing PLA-based resin (LX-175, manufactured by Total Energies Corbion) for 3.5 hours.

[0371] PLA-2 was prepared by hydrolyzing PLA-based resin (Ingeo3251D, manufactured by Nature Works) for 1.5 hours.

[0372] PLA-3 was prepared by hydrolyzing PLA-based resin (L-175, manufactured by Total Energies Corbion) for 5.5 hours.

[0373] PLA-4 was prepared by hydrolyzing PLA-based resin (LX-175, manufactured by Total Energies Corbion) for 1.5 hours.

[0374] PLA-5 was prepared by hydrolyzing PLA-based resin (LX-175, manufactured by Total Energies Corbion) for 4.5 hours.

[0375] PLA-6 was prepared by hydrolyzing PLA-based resin (LX-175, manufactured by Total Energies Corbion) for 2.5 hours.

[0376] The melting point, MFR (190℃, 2.16kg), MFR (210℃, 2.16kg), content of 3HB units, content of 3HH units, and weight-average molecular weight of polylactic acid resins were determined by the methods described above.

[0377] The physical properties of PLA-1 to PLA-6 are shown in Table 1 below.

[0378]

[0379] (Crystallization nucleating agent)

[0380] PETL: Pentaerythritol (manufactured by Taisei Chemical Co., Ltd., Neutizer P)

[0381] (Examples 1-10, Comparative Examples 1-3, Reference Example 1)

[0382] The materials described above were fed into a twin-screw extruder according to the formulation in Table 2 below, and melt-blended at a set temperature of 165°C to obtain granules. These granules were then dried overnight at 80°C to obtain a granular raw material composition.

[0383] Next, use Figures 1-3 The fiber manufacturing apparatus shown in the figure obtains a compounded fibrous melt (fibrous melt compound) from a granular raw material composition at a single-hole extrusion rate of 0.045 g / min / hole (gear pump speed 15 rpm) under the conditions of extruder temperature 180°C and nozzle temperature 192°C.

[0384] Then, gas (air) at a set temperature of 185°C was blown onto the fibrous melt blend at a rate of 6140 NL / min, thereby producing a meltblown nonwoven fabric as a fibrous structure containing fibers.

[0385] It should be noted that the fiber structure was manufactured using nozzles with a width of 600 mm, a hole diameter of 0.15 mm, a hole spacing of 0.35 mm, and a total of 1207 holes. The distance (DCD) between the nozzle hole and the collecting surface of the collector (conveyor belt) was set to 175 mm. The ambient temperature around the fiber manufacturing device was 22°C.

[0386] (Example 11)

[0387] Using the materials described in Table 2 below, a gas (air) at a set temperature of 185°C was blown onto the fibrous melt blend at a rate of 3000 NL / min. Otherwise, a meltblown nonwoven fabric containing fibers was manufactured as a fibrous structure by the same operation as in Examples 1 to 10.

[0388] (Example 12)

[0389] Using the materials described in Table 2 below, a gas (air) at a set temperature of 185°C was blown onto the fibrous melt blend at a rate of 2000 NL / min. Otherwise, a meltblown nonwoven fabric containing fibers was manufactured as a fibrous structure by the same operation as in Examples 1 to 10.

[0390] The physical properties were determined using the following methods.

[0391] (Physical properties of the raw material composition)

[0392] The weight-average molecular weight and MFR (190°C, 2.16 kg) of the raw material composition were determined by the methods described above.

[0393] (Maximum load, elongation at maximum load point, and elongation at break of the fiber structure in the CD and MD directions)

[0394] The maximum load, elongation at the maximum load point, and elongation at the breaking point were measured in the CD and MD directions of the fiber structure.

[0395] It should be noted that the maximum load, maximum load point elongation, and fracture point elongation in the CD and MD directions were measured using a constant-speed elongation tensile testing machine based on JIS B7721:2018 "Tensile testing machine / compression testing machine - Calibration and verification method for force measurement system".

[0396] As a constant-speed elongation tensile testing machine, a universal testing machine (RTG-1210 manufactured by A&D Corporation) was used.

[0397] First, cut out a test piece (width: 8 mm, length: 40 mm) from the fiber structure.

[0398] Next, the test specimen is mounted on the tensile testing machine with a chuck spacing of 20 mm at the initial load. In other words, the chuck spacing is set to 20 mm when the initial load is applied to the test specimen. The initial load is set to the point where the test specimen is stretched by hand until it does not relax.

[0399] Then, a load was applied at a tensile speed of 20 mm / min until the test piece broke, and the maximum load in the CD and MD directions was measured.

[0400] In addition, the maximum load point elongation and fracture point tension in the CD and MD directions are calculated using the following formula.

[0401] Maximum load point elongation (%) = [(Chuck spacing at maximum load - Chuck spacing when initial load is applied to the test piece) / Chuck spacing when initial load is applied to the test piece] × 100 (%)

[0402] Elongation at break (%) = [(Chuck spacing at break - Chuck spacing when initial load is applied to the test piece) / Chuck spacing when initial load is applied to the test piece] × 100 (%)

[0403] The measured values ​​are shown in Table 2 below.

[0404] (Other physical properties)

[0405] The unit area weight and thickness of the fiber structure, the weight-average molecular weight and MFR of the resin composition (190℃, 2.16kg), the average fiber diameter and coefficient of variation of the fibers in the fiber structure, and the extrapolated glass transition onset temperature (T0) of the polylactic acid resin component in the above fibers. ig (PLA) and the glass transition temperature at the midpoint (T) mg (PLA)) and the ratio of the total area of ​​the island portions in the cross-section of the fiber to the cross-sectional area of ​​the fiber (also known as the "total area ratio of the island portions in the cross-sectional area of ​​the fiber") are determined by the method described above.

[0406] It should be noted that the proportion of the total area of ​​the islands in the fiber cross-section is determined based on the fiber structure. The cross-sections of three or more fibers are randomly selected from the captured images, and the proportion of the area of ​​the islands (with a minimum diameter of 100 nm or more) composed only of P3HA or PLA resin in the fiber cross-section is calculated.

[0407] The measured values ​​are shown in Table 2 below.

[0408] In addition, TEM images of the fiber cross sections of Example 3 and Comparative Example 3 are shown respectively. Figure 4 , 5 Additionally, SEM images of the fiber structures of Example 3 and Comparative Example 3 are shown below. Figure 6 , 7 Furthermore, the DSC curves of the fibers from Example 3 and Comparative Example 3 are shown below. Figure 8 , 9 .

[0409] The evaluation experiment was conducted using the following methods.

[0410] (Fracturing energy and fracture difficulty in the CD and MD directions of fiber structures)

[0411] Using a universal testing machine (e.g., RTG-1210, manufactured by A&D) based on JIS B7721:2018 "Tension testing machine / compression testing machine - Calibration and verification method for force measurement system", tensile tests were performed on test pieces (fiber structure) with a width of 8 mm and a length of 40 mm, with a chuck spacing of 20 mm and a tensile speed of 20 mm / min, and the data of "load (N)-displacement (mm) curve" were obtained.

[0412] Then, the integral of the above data up to the point of fracture is taken as the fracture energy (mJ), and the fracture energy per unit cross-sectional area (mJ / mm²) is calculated using the following formula. 2 ).

[0413] Fracture energy per unit cross-sectional area (mJ / mm) 2 = Fracture energy (mJ) / (width of test piece (mm) × thickness of test piece (mm))

[0414] Hereinafter, the "fracture energy per unit cross-sectional area" will also be referred to as "fracture energy".

[0415] The fracture energy was measured in the CD and MD directions of the fiber structure, respectively.

[0416] The measured values ​​are shown in Table 2 below.

[0417] (Collection efficiency of virus droplets in fibrous structures)

[0418] The viral droplet capture efficiency (VFE) was determined for the fibrous structure. The viral droplet capture efficiency (VFE) was determined based on JIS T9001:2021 "Performance requirements and test methods for medical masks and general masks".

[0419] It should be noted that the virus droplet capture efficiency refers to the capture efficiency of viruses attached to particles.

[0420] The measured values ​​are shown in Table 2 below.

[0421] (Based on pressure loss of fiber structures)

[0422] Pressure loss based on fiber structure was measured.

[0423] Pressure loss was determined based on JIS T9001:2021 "Performance requirements and test methods for medical masks and general masks".

[0424] The measured values ​​are shown in Table 2 below.

[0425] (Home compostable)

[0426] The compostability of fibrous structures was evaluated.

[0427] Home compostability was evaluated based on the following benchmarks.

[0428] ○: In a composting environment at 28°C, either the degree of biodegradability (absolute value) or the degree of biodegradability (relative value) is 90% or more within 12 months.

[0429] ×: In a composting environment at 28℃, both the absolute and relative biodegradability do not exceed 90% within 12 months.

[0430] It should be noted that the degree of biodegradability (relative value) refers to the degree of biodegradability when the saturated biodegradability of cellulose, which is used as the reference material, is set to 100.

[0431] In addition to setting the biodegradability test temperature to 28℃, the determination of biodegradability was based on JIS K6953-2.

[0432] The results are shown in Table 2 below.

[0433] (Biodegradability in seawater)

[0434] The biodegradability of fibrous structures in seawater relative to the number of days was determined based on ASTM D6691. It should be noted that, as a reference example 2, cellulose powder was prepared, and the biodegradability of the cellulose powder in seawater relative to the number of days was also determined.

[0435] The results are shown in Figure 10 .

[0436]

[0437] As shown in Table 2, the fiber structures of Examples 1 to 12 within the scope of this invention have high fracture energy.

[0438] On the other hand, Comparative Example 1, which does not contain polylactic acid resin, and Comparative Examples 2 and 3, which have island structures with a total proportion of islands in the fiber cross-section of 8.8% and 15.3% of the fiber cross-sectional area, respectively, have low fracture energy.

[0439] Therefore, it can be seen that, according to the present invention, a fibrous structure that is not easily broken can be provided.

[0440] It should be noted that Reference Example 1, which does not contain poly(3-hydroxyalkanoate) resin, has a high fracture energy. Therefore, it is clear that the technical problem of providing a fibrous structure that is not easily broken is a unique technical problem for fibers containing poly(3-hydroxyalkanoate) resin.

[0441] In addition, as shown in Table 2, the VFE was higher in Examples 1 to 12 compared to Comparative Examples 1 to 3.

[0442] Therefore, according to the present invention, a fiber structure with high particle capture efficiency can be provided.

[0443] Here, as Figure 6 As shown, in Example 3, aesthetically pleasing fibers of a certain fineness were obtained. On the other hand, as... Figure 7 As shown, in Comparative Example 3, the location where nodules formed in the fibers was identified.

[0444] It is believed that the fibers of the present invention are made by fully mixing poly(3-hydroxyalkanoate) resin and polylactic acid resin to form aesthetically pleasing fibers of a certain fineness, resulting in high particle capture efficiency of the fiber structure.

[0445] Furthermore, as shown in Table 2, in Examples 1-12, the compostability was superior compared to Reference Example 1. Additionally, as... Figure 10 As shown, in Examples 2, 3, 6-8, the biodegradability in seawater is superior compared to Reference 1.

[0446] Therefore, it can be understood that, according to the present invention, a fibrous structure with excellent biodegradability can be provided.

Claims

1. A fiber comprising a resin composition, The resin composition comprises a poly(3-hydroxyalkanoate) resin and a polylactic acid resin, wherein, relative to 100 parts by weight of the total poly(3-hydroxyalkanoate) resin and the polylactic acid resin, it comprises 50 to 99 parts by weight of the poly(3-hydroxyalkanoate) resin. The cross-section of the fiber does not have an island structure containing islands with a minimum diameter of 100 nm or more; or it has an island structure containing one or more islands, where the total area of ​​the islands is less than 5% of the cross-sectional area of ​​the fiber. The average fiber diameter of the fiber is less than 5 μm.

2. The fiber according to claim 1, wherein, The coefficient of variation of the fiber diameter is less than 0.

30.

3. The fiber according to claim 1 or 2, wherein, In the fiber, the difference between the extrapolated glass transition start temperature and the intermediate glass transition temperature derived from the polylactic acid resin component is greater than 2.0°C.

4. The fiber according to claim 1 or 2, wherein, The melt flow rate of the resin composition at 190°C and 2.16 kg load is 20~1500 g / 10 min.

5. The fiber according to claim 1 or 2, wherein, The poly(3-hydroxyalkanoate) resin is poly(3-hydroxybutyrate-copolymer-3-hydroxyhexanoate).

6. A fibrous structure comprising the fibers of claim 1 or 2.

7. The fiber structure according to claim 6, wherein it is a spunbond nonwoven fabric or a meltblown nonwoven fabric.

8. A method for manufacturing fibers by melt spinning, the method comprising: A process of melting a raw material composition comprising poly(3-hydroxyalkanoate) resin and polylactic acid resin. The raw material composition comprises 50-99 parts by weight of the poly(3-hydroxyalkanoate) resin, relative to a total of 100 parts by weight of the poly(3-hydroxyalkanoate) resin and the polylactic acid resin. The polylactic acid resin has a melt flow rate of 40~1500g / 10min at 190℃ and 2.16kg load.

9. The method for manufacturing fibers according to claim 8, wherein, The polylactic acid resin has a weight-average molecular weight of 20,000 to 120,000.

10. A method for manufacturing a fiber structure, the method comprising: A fibrous structure comprising the fiber is manufactured by the fiber manufacturing method according to claim 8 or 9. The melt spinning method is either melt-blowing or spunbonding.

Citation Information

Patent Citations

  • Nonnlinear encoder

    JP1978056960A

  • Fibers containing polyhydroxyalkanoate copolymer / polylactic acid polymer or copolymer blend

    JP2004532360A

  • Transformed microorganism for producing PHA copolymer comprising 3HH monomer unit at high composition rate and method for producing PHA using same

    WO2019142845A1

  • Method for producing nonwoven fabric

    WO2019142920A1